Effect of prenatal EPA and DHA on maternal and umbilical cord blood cytokines - Mozurkewich, Ellen L.; Berman, Deborah R.; Vahratian, Anjel; Clinton, Chelsea M.; Romero, Vivian C.; Chilimigras, Julie L.; Vazquez, Delia; Qualls, Clifford; Djuric, Zora (BMC pregnancy and childbirth, 2018)
Background Investigators have hypothesized that omega-3 fatty acid supplementation may modulate the immune response. However, available evidence is conflicting. We performed this study to investigate the effect of prenatal eicosapentaenoic acid (EPA)- and docosahexaenoic acid (DHA)-rich fish oil supplementation on maternal and fetal cytokine production. Methods This study is a secondary analysis of a randomized controlled trial designed to assess whether prenatal EPA- or DHA-rich fish oil supplementation would prevent perinatal depressive symptoms among women at risk. Enrolled participants received EPA-rich fish oil (1060 mg EPA plus 274 mg DHA), DHA-rich fish oil (900 mg DHA plus 180 mg EPA) or soy oil placebo. Maternal venous blood was collected at enrollment (12–20 weeks gestation) and after supplementation (34–36 weeks gestation). Umbilical cord blood was collected at delivery. We analyzed stored plasma specimens for 16 human cytokines using multiplex immunoassays. Maternal and cord blood cytokine levels were compared among the treatment groups. Associations of serum DHA and EPA with maternal and cord blood cytokines were explored via regression analysis. Results We enrolled 126 women, of whom 118 completed the trial. Prenatal supplementation with EPA-rich fish oil significantly lowered maternal IL6, IL15, and TNFα concentrations. However, supplementation with DHA-rich fish oil had no significant effect on maternal cytokine profiles. Maternal serum DHA fraction was significantly associated with IL1α, and maternal serum DHA and EPA fractions were significantly associated with IL 10 concentrations after supplementation. Compared with placebo, supplementation with EPA- or DHA-rich fish oils had no significant effect on cord blood cytokine concentrations. Conclusions Prenatal supplementation with EPA-rich fish oil significantly reduced levels of several inflammatory cytokines in maternal plasma, while prenatal DHA-rich fish oil had no significant effect on cytokine concentrations. Supplementation with EPA- and DHA- rich fish oil had no significant effect on umbilical cord blood cytokine concentrations. Trial registration Clinical Trial Registration: registration number NCT00711971 7/7/2008.